Game-related volleyball skills that influence victory - Silva, M.; Lacerda, D.; Joao, P. V. (Journal of Human Kinetics, 2014)
The aim of the present study was to identify the volleyball skills that discriminate in favour of victory. Twentyfour games (n=24) from the Senior Men's Volleyball World Championship played in Italy in 2010 were chosen and analyzed with Data Volley software. The discriminating function was used to identify the discriminating variables, using a canonical structuring coefficient of |SC| . .30. The results suggest that service points, reception errors, and blocking errors were the discriminating variables that identify the final outcome of the match (victory/defeat). Moreover, successful service points were the major variable most likely associated with match success (victory). In this sense, increasing the effectiveness of service should be a top priority in coaching elite volleyball teams.